Non-optimal behaviour of finite element methods for first order hyperbolic problems - Peterson, Todd E.; Shuster, David B. (Zielona Góra: Uniwersytet Zielonogórski)
We investigate two explicit finite element methods for linear scalar first order hyperbolic equations, one using a continuous piecewise-polynomial approximation and one using a discontinuous approximation. Several aspects of the performance of these methods are considered; in particular, the sharpness of some existing error estimates, and crosswind spread estimates. For the discontinuous method, we give a new error estimate for the case of piecewise-constants.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka